Challenging patents: EPO oppositions and appeals - Atkinson, Jonathan D.M. (Henry Stewart Talks, 2021)
Oppositions at the European Patent Office, Components of Opposition, The procedure during the Opposition, Appeal proceedings, Tactics for both Opposition and Appeal proceedings